Selection and allocation of manual traffic control points and personnel during emergencies - Parr, PhD, EIT, Scott A.; Wolshon, PhD, PE, PTOE, Brian; Dixit, PhD, PE, Vinayak (Journal of Emergency Management, 2015)
Manual traffic control is an intersection control strategy in which law enforcement officers allocate intersection right-of-way to turning movements. Many emergency traffic management plans call for manual traffic control in response to oversaturated roadway conditions. This is because it is thought to more effectively move traffic during temporary surges in demand. The goal of this research was to evaluate the current state-of the- practice used by the Army Corps of Engineers (ACE) in selecting intersections for manual traffic control and allocating police personnel to them during emergencies. This research uses the emergency traffic management plans developed by the ACE for nine counties in the Maryland Eastern Shore region. This area encompassing 14,318 intersections of which 74 were selected for manual traffic control during emergencies. This work sought to quantify the correlations that exist between intersection attributes and the ACE' decision to allocate officers to control them. The research findings suggest that US routes, State routes, and emergency evacuation routes are statistically significant in determining the need for police control at intersections. Also significant are intersection on contraflow corridors and intersections near grade separated interchanges. The model also determined that intersections isolated from evacuation routes and county exits were more likely to be selected for manual control, indicating that rural areas may rely on manual traffic control in the absence of multilane highway and freeways. This research also found that intersections involving evacuation routes, contraflow corridors, and grade separated interchanges may warrant additional police personnel (two or more officers) for manual traffic control.